2018
DOI: 10.1177/000313481808401033
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Quality Improvement Project to Decrease Infection-Related Ventilator Events in Trauma Patients at a Community Teaching Hospital

Abstract: Ventilator-associated pneumonia (VAP) is linked to increased morbidity and mortality and clinical protocols (VAP bundles) have evolved to minimize VAP. In 2009, a quality improvement project was implemented at our institution to decrease VAP rates in adult trauma patients. AVAP prevention committee was developed, and formal evidence-based education for the nursing and physician staff was introduced. During the study period (2009–2016), 2380 patients required ICU admission to our Level II trauma center. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The impact of training and educational activities on VAP prevention strategies has been shown to improve the compliance of healthcare workers to VB and thereby reduction in the incidence of VAP. 13 15 A continuous educational program, including of teaching, video presentation, seminars and group discussion, repeat training of new employees, and continuous educational activities of healthcare workers in a 20-bed ICU for a 2-year period, has shown to improve the median composite score from a baseline of 2–5 points over time and VAP incidence also decreased by 51%. 16 Another study also has shown that education and training of staff nurses for VB for a certain period do not lead to reduction in the incidence of VAP; however, intensive and continued training, bedside skill demonstration, and feedback are essential.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of training and educational activities on VAP prevention strategies has been shown to improve the compliance of healthcare workers to VB and thereby reduction in the incidence of VAP. 13 15 A continuous educational program, including of teaching, video presentation, seminars and group discussion, repeat training of new employees, and continuous educational activities of healthcare workers in a 20-bed ICU for a 2-year period, has shown to improve the median composite score from a baseline of 2–5 points over time and VAP incidence also decreased by 51%. 16 Another study also has shown that education and training of staff nurses for VB for a certain period do not lead to reduction in the incidence of VAP; however, intensive and continued training, bedside skill demonstration, and feedback are essential.…”
Section: Discussionmentioning
confidence: 99%
“…VAP is also a complication with some evidence of a degree of preventability. 25 27 VAP could be a better metric of quality of care if we have a better understanding of how to standardize the reporting of VAP rates between facilities, and thus account for different patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…21,[77][78][79][80][81][82][83] The best-studied interventions to date that have been associated with lower VAE rates in interventional trials include spontaneous awakening trials, spontaneous breathing trials, and conservative fluid management.…”
mentioning
confidence: 99%